Educational innovations beyond technology nurturing leadership and establishing learning organizations - Law, Nancy; Yuen, Allan; Fox, Robert (New York Springer, 2011)
The text explores the concept of innovation, and analyses and compares the different dimensions of innovation found in the case studies presented. It also discusses the anticipated changes to the education profession at a system level, in the coming decade.
Part I. Introduction and Research Methods -- Introduction : context and purpose of the book -- Research methods -- Part II. Classroom level analysis -- Innovations and dimensions of change -- Pedagogical practices and innovations -- Innovating change at the classroom level -- Part III. School level analysis and beyond -- Innovating change at the school level -- Interplay between school level and classroom level factors -- Socio-cultural dimensions of educational change : cross-regional comparisons -- Part IV. Nurturing leadership and establishing learning organizations -- Changing roles in changing times : network of learning organizations for leadership development -- Research into practice : an online case study database for leadership and profession development -- Working with the SITES database of case studies -- Part V. Conclusion -- Thinking beyond technology -- Bibliography.
Keywords: Educational leadership; Educational innovations; Education